Solve the equation A = bh for b.
2 answers:
Answer:
b=a/h
Step-by-step explanation:
Rewrite the equation as bh=a
Divide each term by h and simplify
b=a/h
Answer:
You have to divide both sides by h, in order to make b the subject :
![A = bh](https://tex.z-dn.net/?f=A%20%3D%20bh)
![A \div h = bh \div h](https://tex.z-dn.net/?f=A%20%5Cdiv%20h%20%3D%20bh%20%5Cdiv%20h)
![\frac{A}{h} = bh \times \frac{1}{h}](https://tex.z-dn.net/?f=%20%5Cfrac%7BA%7D%7Bh%7D%20%20%3D%20bh%20%5Ctimes%20%20%5Cfrac%7B1%7D%7Bh%7D%20)
![\frac{A}{h} = b](https://tex.z-dn.net/?f=%20%5Cfrac%7BA%7D%7Bh%7D%20%20%3D%20b)
![b = \frac{A}{h}](https://tex.z-dn.net/?f=b%20%3D%20%20%5Cfrac%7BA%7D%7Bh%7D%20)
You might be interested in
-2/3 / -15
Find the reciprocal of -15 and multiply:
-2/3 * -1/15
Multiply the numerators and denominators together:
2/45
Answer:
I answered your last question also
2 log3x – 2 logx3 -3 <0
![\mathrm{Subtract\:}2\log ^3\left(x\right)\mathrm{\:from\:both\:sides}](https://tex.z-dn.net/?f=%5Cmathrm%7BSubtract%5C%3A%7D2%5Clog%20%5E3%5Cleft%28x%5Cright%29%5Cmathrm%7B%5C%3Afrom%5C%3Aboth%5C%3Asides%7D)
![2\log ^3\left(x\right)-2logx^3-3-2\log ^3\left(x\right)](https://tex.z-dn.net/?f=2%5Clog%20%5E3%5Cleft%28x%5Cright%29-2logx%5E3-3-2%5Clog%20%5E3%5Cleft%28x%5Cright%29%3C0-2%5Clog%20%5E3%5Cleft%28x%5Cright%29)
![\mathrm{Simplify}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D)
![-2logx^3-3](https://tex.z-dn.net/?f=-2logx%5E3-3%3C-2%5Clog%20%5E3%5Cleft%28x%5Cright%29)
![\mathrm{Add\:}3\mathrm{\:to\:both\:sides}](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3A%7D3%5Cmathrm%7B%5C%3Ato%5C%3Aboth%5C%3Asides%7D)
![-2logx^3-3+3](https://tex.z-dn.net/?f=-2logx%5E3-3%2B3%3C-2%5Clog%20%5E3%5Cleft%28x%5Cright%29%2B3)
![\mathrm{Simplify}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D)
![-2logx^3](https://tex.z-dn.net/?f=-2logx%5E3%3C-2%5Clog%20%5E3%5Cleft%28x%5Cright%29%2B3)
![Multiply\:both\:sides\:by\:-1\:\left(reverse\:the\:inequality\right)](https://tex.z-dn.net/?f=Multiply%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A-1%5C%3A%5Cleft%28reverse%5C%3Athe%5C%3Ainequality%5Cright%29)
![\left(-2logx^3\right)\left(-1\right)>-2\log ^3\left(x\right)\left(-1\right)+3\left(-1\right)](https://tex.z-dn.net/?f=%5Cleft%28-2logx%5E3%5Cright%29%5Cleft%28-1%5Cright%29%3E-2%5Clog%20%5E3%5Cleft%28x%5Cright%29%5Cleft%28-1%5Cright%29%2B3%5Cleft%28-1%5Cright%29)
![\mathrm{Simplify}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D)
![2lx^3og>2\log ^3\left(x\right)-3](https://tex.z-dn.net/?f=2lx%5E3og%3E2%5Clog%20%5E3%5Cleft%28x%5Cright%29-3)
![\mathrm{Divide\:both\:sides\:by\:}2lx^3o;\quad \:l>0](https://tex.z-dn.net/?f=%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D2lx%5E3o%3B%5Cquad%20%5C%3Al%3E0)
![\frac{2lx^3og}{2lx^3o}>\frac{2\log ^3\left(x\right)}{2lx^3o}-\frac{3}{2lx^3o};\quad \:l>0\\](https://tex.z-dn.net/?f=%5Cfrac%7B2lx%5E3og%7D%7B2lx%5E3o%7D%3E%5Cfrac%7B2%5Clog%20%5E3%5Cleft%28x%5Cright%29%7D%7B2lx%5E3o%7D-%5Cfrac%7B3%7D%7B2lx%5E3o%7D%3B%5Cquad%20%5C%3Al%3E0%5C%5C)
![\mathrm{Simplify}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D)
![g>\frac{2\log ^3\left(x\right)-3}{2lx^3o};\quad \:l>0](https://tex.z-dn.net/?f=g%3E%5Cfrac%7B2%5Clog%20%5E3%5Cleft%28x%5Cright%29-3%7D%7B2lx%5E3o%7D%3B%5Cquad%20%5C%3Al%3E0)
Step-by-step explanation:
You never gave a question therefore there is no answer without a question
The answer to your question is option b